Characterization of the food intake and nutritional profile of oral cavity cancer survivors and the adherence degree to cancer prevention recommendations issued by the World Cancer Research Fund and the American Institute for Cancer Research Institute - Gislaine Barbosa Bezerra; Renata Brum Martucci; Cristiane Ferreira Rodrigues (Universidade do Estado do Rio de Janeiro, 2021)
Introduction: Survivors of oral cavity cancer (OCC) under control usually have numerous sequelae resulting from oncological treatment, which can compromise their diet and, by extension, meet the guidelines for diet and proper weight issued by the World Cancer Research Fund International-WCRF and the American Institute for Cancer Research-AICR. Objective: To evaluate the dietary profile and nutritional status of oral cancer survivors and verify the degree of their adherence, the guidelines for healthy eating and body weight issued by WCRF/AICR. Method: Cross-sectional study which assessed the nutritional status by the Subjective Global Assessment produced by the patient (PG-SGA) and body mass index (BMI) of 20 patients. Data such as social condition and clinical history were collected from medical records. Food consumption was assessed using a 30-day food diary. Food data and body weight received a score of points according to a greater or lesser degree of adherence to WCRF/AICR recommendations. Results: 80% of patients were moderately malnourished or suspected of malnutrition by PG-SGA. According to BMI 10% of participants were malnourished, 45% eutrophic and 35% were overweight. An average score of 2.64 ± 0.55 adherence to the recommendations of adequate weight and healthy eating was found, showing compliance with less than 50% of the WCRF/AICR recommendations. Conclusion: Survivor patients of OCC patients from the present study are at risk of malnutrition or have moderate malnutrition; and have high symptomology, which negatively impacts food intake and adherence to recommendations of WCRF/AICR.